WHY DOES THE STRUGGLE AROUND SRT CONTINUE TO THIS DAY? - Chubykalo, A.; Espinoza, A.; Kuligin, V.; Korneva, M. (International Journal of Research -GRANTHAALAYAH, 2019)
The purpose of this article is not to criticize the theory of relativity, but to try to understand why, despite more than a century of dominance in physics, it is constantly criticized by physicists. In this paper, a thorough analysis of A. Einstein’s theory of relativity is carried out. It relies on philosophical, physical-mathematical, logical-historical methods of investigation. It is shown that in SRT there is an error in the physical interpretation of the mathematical formalism of the Lorentz transformation (epistemological error). Therefore, the interpretation of the SRT phenomena contains logical contradictions and paradoxes. It is also shown that a consistent interpretation can be given for the Lorentz transformation within the framework of classical space-time representations. It is established that the real speed of the relative motion of inertial reference frames in is greater than the speed entering the Lorentz transformation. A new explanation is offered for relativistic phenomena without violating logic and without paradoxes. The results are of great importance for the description of relativistic phenomena in physical theories, and also for applied disciplines, for example, for the theory of cyclic accelerators, etc.